2005
DOI: 10.1272/jnms.72.387
|View full text |Cite
|
Sign up to set email alerts
|

An Asymptomatic Heterozygous Female with Fabry Disease: Implications for Enzyme Replacement Therapy

Abstract: We report an asymptomatic female with Fabry disease immunohistochemically diagnosed by renal biopsy. She was initially diagnosed as having nephrotic syndrome, and renal biopsy was performed for pathological diagnosis. The renal specimen revealed non-specific findings (minor glomerular abnormalities) for nephrotic syndrome. Numerous laminated bodies in glomerular epithelial cells in electron microscopic findings and accumulations of ceramidetrihexoside immunohistochemically were observed and she was diagnosed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…in chronic kidney disease patients who were not on dialysis was found to be 0.2% by Yeniçerio glu (0.4% in male, 0.0% in female) [19]. Although FD can coexist with several renal diseases, including IgA nephropathy, lupus nephritis, membranous GN, and crescentic nephritis, nephrotic syndrome as the first clinical clue of Fabry-related kidney damage remains rare, with only nine cases reported (shown in Table 2), of which five were male and four were female [20][21][22][23][24][25][26][27]. Zarate et al reported a 16-year-old male patient with minimal change nephrotic syndrome and underlying FD in 2010, who was responded well to steroid and ERT treatment, eventually his proteinuria became undetectable [26].…”
Section: Discussionmentioning
confidence: 99%
“…in chronic kidney disease patients who were not on dialysis was found to be 0.2% by Yeniçerio glu (0.4% in male, 0.0% in female) [19]. Although FD can coexist with several renal diseases, including IgA nephropathy, lupus nephritis, membranous GN, and crescentic nephritis, nephrotic syndrome as the first clinical clue of Fabry-related kidney damage remains rare, with only nine cases reported (shown in Table 2), of which five were male and four were female [20][21][22][23][24][25][26][27]. Zarate et al reported a 16-year-old male patient with minimal change nephrotic syndrome and underlying FD in 2010, who was responded well to steroid and ERT treatment, eventually his proteinuria became undetectable [26].…”
Section: Discussionmentioning
confidence: 99%
“…Como é uma doença relacionada ao cromossomo X, os homens apresentam as formas graves da doença e transmitem para todas as filhas, mas não aos filhos. Segundo a literatura, cerca de 10% das heterozigotas desenvolve insuficiência renal, o que pode ser explicado pela hipótese de inativação do X (15,18) . Segundo essa hipótese, um dos cromossomos X nas mulheres é aleatoriamente inativado nas células, numa tentativa de igualar a expressão de genes ligados ao X nos sexos masculino e feminino (15) .…”
Section: Discussionunclassified
“…Germain et al (2002) observed progressive hearing loss, with a significantly higher prevalence in patients with renal failure or cerebrovascular lesions (GERMAIN et al, 2002). According to the literature, around 10% of heterozygous women develop kidney failure (INAGAKI et al, 2005;WARNOCK et al, 2015).…”
Section: Symptomsmentioning
confidence: 99%